Understanding the Barriers and Enablers to Using Outdoor Spaces in Nursing Homes: A Systematic Review. (24th May 2019) - van den Berg, Maayken E L; Winsall, Megan; Dyer, Suzanne M; Breen, Fidelma; Gresham, Meredith; Crotty, Maria
Abstract: Background and Objectives: Despite acknowledged benefits of residents in nursing homes spending time outdoors, little is known about factors related to their use of outdoor space. This systematic review summarizes reported barriers and enablers to nursing home residents' use of outdoor spaces. Research Design and Methods: Multiple databases were searched to May 2018. Qualitative or mixed methods studies describing barriers/enablers to use of outdoor areas by residents of nursing homes (aged 65 years and older), as reported by residents, staff, or family members were included. Study quality rating, thematic analysis, and stratified analyses were performed and confidence in findings assessed using GRADE-CERQual. Results: Twenty-four studies were included. Nineteen collected data from residents, 15 from staff/caregivers, 7 from families. Major themes and key findings concerned: design of the outdoor area (importance of garden greenery and built features), safety concerns and staffing issues, weather and seasons (appropriate shade and shelter), design of the main building (easy to open doors and nearby access points) and social activities. Conclusions and Implications: Providing gardens with seasonal plants and interactive features, weather protected seating, manageable doors at accessible thresholds, planned social activities, and appropriate clothing are fundamental to facilitate nursing home residents' access to the outdoors. Cultural change at an organizational level, addressing perceptions of safety as a barrier is important. Incorporation of the recommendations in this review by architects, facility managers, and policy makers in the design and management of nursing homes, may increase use of outdoor areas and improve the quality of life of residents. Registration: The protocol is registered in Prospero (CRD42018100249).